Pengembangan Media Pembelajaran Saintifik berbasis Multimedia melalui Model Discovery Learning - Mohamad Fatih (Jurnal Pendidikan : Riset dan Konseptual, 2018)
Based on the observations conducted in August-September in elementary school on learning conducted by elementary school teachers in Blitar there is learning, media is still using conventional media in the form of images. Solutions to improve the learning conditions that have been found above by developing learning media in accordance with the curriculum, characteristics of student development and the characteristics of learning materials. This research method using R & D. There are four phases in the process of making instructional media, (1) basic competence analysis and learning indicators, (2) character analysis and learning materials, (3) analysis of student characteristics, and (4) making of scientific learning media with Power Pont application. Media feasibility test results by media and material experts are rated "good" and worthy of trials with an average score of 4.0 and 4.1. In the test subjects of respondents gave an assessment with an average score of 4.25. Based on the results of the validation of experts shows that the media developed have the feasibility in terms of appearance and content. Based on the eligibility criteria then the Power Point Media Material Save Life on Humans has the eligibility criteria "Very Good".